Economics - Taylor, Timothy, 1960-; Teaching Company (Chantilly, VA : Teaching Co., 2005)
We are all economists--when we work, buy, save, invest, pay taxes, and vote. It repays us many times over to be good economists. Economic issues are active in our lives every day. However, when the subject of economics comes up in conversation or on the news, we can find ourselves longing for a more sophisticated understanding of the fundamentals of economics. This lecture series will help you think about and discuss these and other economic issues that affect you and the nation every day--interest rates, unemployment, personal investing, budget deficits, globalization, and many more--with a greater level of knowledge and sophistication.
Lecturer: Timothy Taylor
Keywords: Business; Economics; Money